2021
DOI: 10.1021/acs.chemmater.1c02444
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Oxygen and Hydrogen Defects in Modulating the Optoelectronic Properties of P-Type Metal Oxide Semiconductors

Abstract: P-type metal oxide semiconductors have been developed for solar fuel generating systems, but efforts to improve energy efficiency remain challenging due to the limited understanding and control of defects. Herein, p-type CuBi2O4 was chosen as a prototypical model system to investigate the presence and mitigation of inevitable defects, including hydrogen impurities and oxygen vacancies. By a combination of experimental and theoretical analyses, these defects were determined to be shallow donors which reduce p-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…From Figure i, the negative slopes demonstrate the p-type semiconductor characteristics. The hole density ( N A ) can be decided from the slopes of the tangent line of the linear portion in the Mott–Schottky plots, and for io-CBO photocathodes, the different N A values calculated are of the same order of magnitude, which can be derived from the distinction of pore sizes . In addition, according to the x -intercept, the flat-band potentials of io-CBO 200 and io-CBO 400 are 1.34 and 1.38 eV, respectively, which are consistent with reported results .…”
Section: Resultssupporting
confidence: 87%
“…From Figure i, the negative slopes demonstrate the p-type semiconductor characteristics. The hole density ( N A ) can be decided from the slopes of the tangent line of the linear portion in the Mott–Schottky plots, and for io-CBO photocathodes, the different N A values calculated are of the same order of magnitude, which can be derived from the distinction of pore sizes . In addition, according to the x -intercept, the flat-band potentials of io-CBO 200 and io-CBO 400 are 1.34 and 1.38 eV, respectively, which are consistent with reported results .…”
Section: Resultssupporting
confidence: 87%
“…The sharpness of signals from thin-film semiconductors is related to a modification of the semiconductor optical properties (the complex index of refraction) due to the perturbation of the charge carrier band population by the pump pulse. 30,38 Kinetic traces at 530 nm with 400 nm excitation (Fig. 3(g) and 3(h)) were well fitted by three exponential functions with three-time constants.…”
Section: Resultsmentioning
confidence: 78%
“…Taking these results together, we suggested that adding the LNO buffer layer can improve carrier dynamics (also improve the onset potential and the fill factor) and mitigated recombination (higher photocurrent and negligible current transients). [30][31][32] Such an enhanced performance may be due to the increased light-harvesting of LNO/BFO films as LNO is light-dark by eye, studied by UV-vis absorption spectra. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The main reasons for this discrepancy are recombination of the photocarriers within the semiconductor and the inefficient electrochemical catalytical process. [17][18][19] Analogous to other transition metal oxide semiconductors, CBO exhibits polaron transport, which can signicantly reduce charge mobility and thus limit the diffusion length of photocarriers. 20,21 As a result, the photocarriers only present a diffusion path of 45 nm, and a very low percentage of charge carriers can participate in the surface reaction.…”
Section: Introductionmentioning
confidence: 99%